Does Weaker Employment Protection Lower the Cost of Job Loss? - Marco Francesconi; Daniela Sonedda (CESifo GmbH, 2024)
Leveraging a major Italian reform enacted in June 2012 that eroded employment protection to workers on permanent contracts, we use detailed administrative data to estimate how this reduction affected the cost of job loss. We employ a stacked-by-event research design, which compares workers moving into nonemployment before and after the reform. Weakening employment protection led to additional penalties in terms of lower re-hiring earnings and lower re-employment probabilities. Heterogeneous effects of the reform deepened pre-existing divides, penalizing more, among others, young workers and workers living in the South.
Keywords: J63; J65; J30; J41; J68; 330; layoffs; employment protection; dual labor markets; difference-in-differences; Italy